2005
DOI: 10.1002/arch.20075
|View full text |Cite
|
Sign up to set email alerts
|

Expression and regulation of phospholipase A2 in venom gland of the chinese honeybee,Apis cerana cerana

Abstract: Phospholipase A(2) (PLA(2)) is one of the components of bee venom with a wide range of pharmacological functions. It operates as a major allergen working with other venom components to defend the colony from intruder. In the present study, the cDNA sequence of the Ac-pla(2) gene from cDNA library of the venom gland of Apis cerana was compared with the amplified corresponding region of genomic DNA. The result showed that the Ac-pla(2) gene consisted of four exons and three introns. Southern blot showed that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…Soldatova et al (1998) also found that recombinant BvHya expressed in Tn cells appeared as a double band of 43 to 44 kDa with different glycosylations. Our results are consistent with these previous reports (Li et al, 2005;Altmann et al, 1991;Soldatova et al, 1998). Since the glycosylation of recombinant protein is an important factor that affects protein function, the present study combined with our previous findings may lay a new scientific basis for the molecular biological utilization of AccPLA 2 in the future.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Soldatova et al (1998) also found that recombinant BvHya expressed in Tn cells appeared as a double band of 43 to 44 kDa with different glycosylations. Our results are consistent with these previous reports (Li et al, 2005;Altmann et al, 1991;Soldatova et al, 1998). Since the glycosylation of recombinant protein is an important factor that affects protein function, the present study combined with our previous findings may lay a new scientific basis for the molecular biological utilization of AccPLA 2 in the future.…”
Section: Discussionsupporting
confidence: 93%
“…The results indicate that there was crossreaction between the expressed fusion protein in Tn cells and anti-AmPLA 2 polyclonal serum. One mixed venom sample of Chinese honeybee was reported to have three bands detected for the natural AccPLA 2 with molecular weight 15 kDa using the antiAmPLA 2 antibody, which was caused by the characters of BvPLA 2 glycosylation (Li et al, 2005). These results also indicate that the expressed AccPLA 2 protein can be glycosylated in Tn cells.…”
Section: Sds-page and Western Blot Analysismentioning
confidence: 82%
See 2 more Smart Citations
“…PLA2 is involved in several cellular signaling pathways, such as inflammation 346 and apoptosis 347 . PLA2 is also found in the venom of many venomous animals such as bees [348][349][350] , wasps 351 , spiders 352,353 , scorpions 354 , centipedes 355 , snakes 356 , gila monsters 357 , cuttlefish 358 , sea anemones 359 , cone snails 360 , and others, creating an interesting example of convergent evolution 361 . These PLA2s often have neurotoxic and hemorrhagic activity, although some venom PLA2s are toxic while having no catalytic activity, acting as ligands for receptors on neurons [362][363][364] .…”
Section: Introductionmentioning
confidence: 99%